KORELASI PENERAPAN PROGRAM SISTEM SMK3 DENGAN KINERJA KARYAWAN - Indah Nur Aini; Rifaatul Laila Mahmudah; Asih Media Yuniarti; Hesti Yusiani (MEDICA MAJAPAHIT, 2025)
The national development program entering the industrializatorcion era is marked by increasing industrial growth, so it needs to be balanced with improving the quality of the workforce and the implementation of the occupational health and safety management system (OHS). This study airmed to study the relationship between implementation the OHS and employee performance of PT Albany Indonesia Tuban.This study used cross sectional turth simple random sampling technique.Simple size was 37 employees at PT Albany Indonesia .Data collected using a OHS and Performence employees questionnairies.The results showed that there was a relationship between implementation the OHSwith employee performance, as by the results of spearman rank test,( p value = 0.007), this indicated that the correlation was statistically significant.The implementation of optimal OHS for employees is directly related to employee performance, because the implementation of OHS is one way to motivate employees to improve their performance